2014
DOI: 10.1007/s12094-014-1204-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of initial FDG PET/CT in the management plan of patients with locally advanced head and neck cancer

Abstract: Initial FDG PET/CT staging not only improves stage but also affects the management plan in LAHNC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…This is in concordance with literature, reporting a PET/CT-based change in patient management in 6-31% (Table 5) [15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Overallsupporting
confidence: 91%
See 2 more Smart Citations
“…This is in concordance with literature, reporting a PET/CT-based change in patient management in 6-31% (Table 5) [15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Overallsupporting
confidence: 91%
“…Several studies have reported how FDG-PET/CT led to a change in patient management in 6-57% of the cases [15][16][17][18][19][20][21][22][23][24][25][26][27]. This included upstaging, downstaging as well as diagnosing synchronic lesions and distant metastasis.…”
Section: -[ 18 F]-fluoro-2-deoxy-d-glucose (Fdg)-positron Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved staging with the use of imaging might help in avoiding unnecessary surgical interventions, which increases the morbidity of disease without a substantial benefit in the reduction of mortality. On the other hand upstaging can lead to the choice of more aggressive therapies, which may reduce the recurrence rate [ 25 , 26 ].…”
Section: Imaging In the Selection Of Treatmentmentioning
confidence: 99%